2016
DOI: 10.1002/jssc.201600132
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption of modified nucleoside cancer biomarkers by hybrid molecularly imprinted adsorbents

Abstract: Modified adenosine nucleosides have been proposed to be potential DNA-based biomarkers for early diagnosis of tumor and a promising tool for the development of noninvasive prediction systems. However, the low concentration of modified adenosine nucleosides in physiological fluids makes them challenging for both quantitative and qualitative determination. Therefore, materials, which are potentially useful for selective adsorption of nucleobase-containing compounds, were obtained. To obtain the adsorbents, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Consequently, an increased excretion of abnormal amounts of modified nucleosides in the urine of cancer patients can be observed. Therefore, modified nucleosides are widely regarded as potential tumor biomarkers [99,100]. Recently, Zhang et al have reported that the intracellular fluctuations of six endogenous nucleotide levels (AMP, UDP, CTP, ATP, UTP, and GMP) were significantly higher in cancer cells [101].…”
Section: Review Of the Literature Related To Mip-based Sensors Formentioning
confidence: 99%
“…Consequently, an increased excretion of abnormal amounts of modified nucleosides in the urine of cancer patients can be observed. Therefore, modified nucleosides are widely regarded as potential tumor biomarkers [99,100]. Recently, Zhang et al have reported that the intracellular fluctuations of six endogenous nucleotide levels (AMP, UDP, CTP, ATP, UTP, and GMP) were significantly higher in cancer cells [101].…”
Section: Review Of the Literature Related To Mip-based Sensors Formentioning
confidence: 99%
“…To further confirm this study, the same samples were studied with HPLC (Supporting Information ). The ATP (retention time 13.04 min) was not found in the urine sample because of the dilution or other metabolite nucleotides/nucleosides . However, some additional peaks with small concentrations such as uric acid, creatinine, etc.…”
Section: Resultsmentioning
confidence: 99%
“…MIP is highly advantageous, so an artificial recognition unit was considered for the fabrication of bioassay with regards as a means to benefit a replacement for biological antibodies in medical diagnostic and bioassays, and in a wide array of other analytical techniques. In particular, MIPs are widely used as sorbents for SPE applications . The surface imprinting technique is a potential technique to improve the template transfer efficiency from the molecularly imprinted materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many MIP biomarker-targeted sensors ,,,, were developed to test for the presence of a carcinoma. Other interesting MIP biomarker-templated systems were targeted to the presence of an active infection or a specific diseased organ.…”
Section: Applications Of Mipsmentioning
confidence: 99%